Sustainable Impact on Girls’ Lives : Skills Development Programs for Adolescent Girls - World Bank (World Bank, Washington, DC, 2017)
In this note, a relatively small investment in research and evidence can yield lasting impacts onyoung women’s employment and can inform large-scale policies and programs to improve the lives of girls and their communities.We often hear about a looming youth employment crisis in low-income countries. Although governments are spending more than ever before on youth employment programs, these programs rarely target young women explicitly, even though they have lower employment ratesthan young men and face additional socio-cultural barriers. Globally adolescent girls are marginalized in large numbers, and their vulnerabilities and constraints are particularly acute in Sub-Saharan Africa. Young women tend to have less education, so they’re less qualified for jobs. They do not have as much time available for paid work because of their domestic duties and they often do not pursue jobs in high-paying fields because they are not considered suitable for women. There’s also a strong family formation dimension to young women’s employment decisions that doesn’t affect young men in the same way.